PERSPEKTIF HERMENEUTIKA RICOEUR MENYUSURI AGENDA TOLERANSI DI ORGANISASI ISLAM NAHDLATUL ULAMA - Said Romadlan; Ibnu Hamad; Effendi Gazali (Universitas Bunda Mulia, 2020)
ABSTRACT The Perspective of the Ricoeur hermeneutics about tolerance at the Islamic organization Nahdlatul Ulama (NU) focuses on the interpretation process of NU as an influential Islamic organization concerning tolerance to non-Muslims. The understanding of current tolerance is crucial amid strengthening the action of intolerances and discrimination in various forms of intimidation and assault on minority groups. In addition, the interpretation of the meaning of tolerance can be considered to be one of the triggers of radical action, especially when associated with issues of political leadership, the establishment of a place of worship, and so on. Therefore, the purpose of this article is to understand how the process of interpretation done by NU about tolerance toward non-Muslims. The Method in this study was the hermeneutics method of Paul Ricoeur, that emphasizing the interpretation of the text with the distanciation process between text and the reader. The results show that the interpretation process of tolerance is based on the language (verses) of the Qur'an surat al-Hujurat verse 13